DEFINING TERMINALS` EFFICIENCY IN A SEAPORT USING DATA ENVELOPMENT ANALYSIS - Djelovic, Deda (Journal of Applied Engineering Science, 2023)
Efficiency is the capability of a port or terminal to fit the optimum number of inputs to a given output level. In principle, there are three required elements for measuring efficiency: decision making unit (DMU), output variables, and input variables. The measurement of efficiency in production units and the identification of sources of their inefficiency is a precondition to improve performance of any production unit in a competitive environment. Many research studies have been conducted around the world for efficiency assessment in the maritime sector, including ports/terminals utilizing different methods, but in the significant percentage of those studies have been used Data Envelopment Analysis (DEA) and DEA-based approaches. After some general theoretical considerations on port/terminal efficiency and standard approaches for its measuring, elements related to a research of seaport terminals overall efficiency, using DEA-CCR input oriented method is shown. Four port terminals are taken into consideration and their efficiency scores are calculated using appropriate software, based on established data series - values of input/output variables - related to the cargo handling system in the Port of Bar (Montenegro).
Keywords: efficiency, data envelopment analysis, terminals